Memilih Arti Hidup: Telaah Etika Nilai dan Aktualisasi Diri Manusia (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
This article explores the meaning of human life through the lens of value, choice, and ultimate purpose. Drawing from the analogy of nature, the study argues that human existence is likewise structured around meaning rather than randomness. Human beings inevitably encounter diverse and sometimes conflicting values, requiring discernment and responsible decision-making. Not all values carry equal weight; their significance depends on their proximity to the ultimate goal of human life understood in its totality. The paper identifies three fundamental attitudes toward life: a pessimistic stance that perceives life as failure, a hedonistic stance that seeks satisfaction and pleasure, and a constructive stance that embraces life as a meaningful vocation. Through a reflective-ethical approach, the discussion highlights the importance of mission, prioritization, empathetic communication, synergy, and continual self-renewal. Ultimately, the quality of human existence is determined by the values one chooses to uphold and the orientation of life toward a higher, integrative purpose.